ACS and NAFTA : problems and opportunities for Barbados and CARICOM : address... at the luncheon of the Barbados Chamber of Commerce and Industry - Carrington, Edwin W. ([CCS] GeorgetownGY, 1995)
Highlights features of the ACS and NAFTA and notes what they are designed to do. Focuses on the implications of the ACS and NAFTA for CARICOM and Barbados.